Penilaian Profitabilitas Perusahaan dalam Kajian Akuntansi (Studi Kasus pada Perusahaan yang Terdaftar di Indeks Saham Syariah Indonesia) - Heny Rofizar; Husna Hayati; Angga Syahputra; Asmah Savitri (Jurnal Iqtisaduna, 2021)
The Companies are generally founded with certain activities to generating profits. The company's ability to generate profits is called profitability. The assessment of the company's profitability is not only assessed based on the profit account presented in the financial statements. In this case, it is important to do further analysis of profitability in order to describe the profitability and its development as well as the company's financial performance. This study aims to provide a study in the scope of accounting on the assessment of company profitability by combining financial ratios and trend analysis. This study used a quantitative descriptive approach. The researcher first describes the theory or related studies, then applied it to the company, one of constituents of Indonesia Sharia Stock Index (ISSI), PT. Media Nusantara Citra, Tbk by using financial ratios and trend analysis to see the level and development of the company's profitability. From the results of the profitability assessment using financial ratios in the form of Returns on Assets (ROA) and Net Profit Margin (NPM) and trend analysis, the results obtained are that based on ROA and NPM, the profitability of  PT Media Nusantara Citra Tbk for the 2017-2020 period is considered good means the company's financial condition or performance is considered good, where the average ROA is 10.83% and NPM 23.87%, then based on trend analysis, the company's profitability has a tendency that tends to fluctuate.